2019
DOI: 10.1089/ars.2018.7500
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Prion Protein in the Protection of the Human Bronchial Epithelial Barrier Against Oxidative Stress

Abstract: Aim: Bronchial epithelium acts as a defensive barrier against inhaled pollutants and microorganisms. This barrier is often compromised in inflammatory airway diseases that are characterized by excessive oxidative stress responses, leading to bronchial epithelial shedding, barrier failure, and increased bronchial epithelium permeability. Among proteins expressed in the junctional barrier and participating to the regulation of the response to oxidative and to environmental stresses is the cellular prion protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Desmoplakin mediates the connection between intermediate filaments and the junctional plaque at the cell membrane [17][18][19]. There are also several nonstructural proteins found in desmosomes, such as the RhoA regulator kazrin [76], the LRR And PDZ family scaffolding protein erbb2 interacting protein (Erbin) [77], and the prion protein PrPC [74]. Type I hemidesmosomes comprise a group of transmembrane receptors, including a6b4 integrins, 180-kDa bullous pemphigoid antigen (BP180), and cluster of differentiation 151 (CD151).…”
Section: The Main Composition and Associating Molecules Of Epithelial...mentioning
confidence: 99%
See 1 more Smart Citation
“…Desmoplakin mediates the connection between intermediate filaments and the junctional plaque at the cell membrane [17][18][19]. There are also several nonstructural proteins found in desmosomes, such as the RhoA regulator kazrin [76], the LRR And PDZ family scaffolding protein erbb2 interacting protein (Erbin) [77], and the prion protein PrPC [74]. Type I hemidesmosomes comprise a group of transmembrane receptors, including a6b4 integrins, 180-kDa bullous pemphigoid antigen (BP180), and cluster of differentiation 151 (CD151).…”
Section: The Main Composition and Associating Molecules Of Epithelial...mentioning
confidence: 99%
“…In addition to the core structural components mentioned above, proteins with diverse functions attach to the adherens junctions but are not essential for the assembly of the junctional structure. These molecules include but not limited to the transcriptional coactivator YAP [62] and its regulators (Ajuba family proteins and LATS family proteins) [63,64], the Ras homolog (Rho) guanosine triphosphate hydrolase (GTPase) RhoA [65,66], the Rho guanine nucleotide exchange factor epithelial cell transforming 2 (ECT2) [65], the centralspindlin complex protein male germ cell Rac GTPase-activating protein (MgcRacGAP) [65], Rho-associated protein kinase 1 (ROCK1) [67], tyrosine kinases erythroblastic oncogene B2 (ErbB2) and Fps/Fes [68,69], phosphoinositide 3-kinase (PI3K) [70], the tyrosine phosphatase Pez [71], PTEN [72], Ras association domain family member 8 (RASSF8) [73], the prion protein prolinerich protein C (PrPC) [74] and the mechanoreceptor transient receptor potential cation channel subfamily V member 4 (TRPV4) [75]. The core transmembrane proteins of desmosomes include desmoglein and desmocollin, whose ectodomains interact in a heterophilic or homophilic manner with their partners at the adjacent cell membrane.…”
Section: The Main Composition and Associating Molecules Of Epithelial...mentioning
confidence: 99%
“…Furthermore, Anding & Baehrecke (2017) spotted using EM that vacuolations were actually damaged organelles such as mitochondria and lysosomes or could be lipid-filled or autophagic vacuoles. Additionally, the oxidative stress disrupts different epithelial intercellular junctions through protein modification “such as thiol oxidation, phosphorylation, nitration, and carbonylation” in addition to degradation of adherens and desmosomal junction proteins (Rao, 2008; Inumaru et al, 2009; Kouadri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, oral administration of TMM in diabetic animal model also found that elevated glutathione (GSH) level, superoxide dismutase (SOD), and catalase (CAT) activities to be associated with reduced lipid peroxidation 66 . Reduced lipid peroxidation is important to prevent many detrimental effects on airway function which were caused by oxidative stress, including airway hyperresponsiveness 67 , mucus hypersecretion 68 , epithelial shedding 69 , airway smooth muscle contraction 70 , vascular exudation 71 , and increased vascular permeability 72 . Our result also revealed that participants with normal BMI responded better to the supplementation as compared to other categories of BMI.…”
Section: Discussionmentioning
confidence: 99%